Chemotherapy-Induced Fulminant, Severe Hyperactive Delirium in A Patient with A New Diagnosed Multiple Myeloma - Pavlova, Olesya; Weinrebe, Wolfram (Archives of Clinical and Medical Case Reports, 2020)
Multiple myeloma is an incurable haematological malignancy with complex pathogenesis, affecting mostly the elderly and characterized by the presence of monoclonal plasma cells within the bone marrow secreting an abnormal immunoglobulin, which results in gammapathy with organ or tissue injury. The chemotherapy used for the treatment of multiple myeloma causes various adverse effects, including serious psychiatric and cognitive problems, which pose a significant challenge to the clinician, present an impact on the quality of patient’s life and augment hospital stays and health care costs. We reported a clinical case of 73-year-old women with new diagnosed multiple myeloma developing severe, rapidly progressing and persisting hyperactive delirium with psychotic symptoms and mania-episodes during Velcade-Revlimid-Dexamethasone-based treatment. We discuss possible causes, clinical presentation, treatment and deficits maintained after recovery. Our report demonstrates the rare possibility of an association between chemotherapy and the development of combined psychiatric disorders.